EDUCATION OF LOCAL WISDOM TO PREVENT FOREST FIRES IN RIAU PROVINCE: CHALLENGES, POTENTIALS, AND SOLUTIONS - Rian Vebrianto; Zarkasih Zarkasih (Lembaga penelitian dan pengabdian kepada Masyarakat, 2017)
Forest fires are one of the most frequent environmental problems in Riau province, which often comes in large scale; thus, they cause forest degradation that damages economic, ecological and social aspects. The forest fires in Riau primarily caused by weak regulations and their enforcement and the lack of an optimum system or institutional mechanisms to address this issue. One alternative solution that is often forgotten is the role of education in forest fires prevention, particularly in the education of local wisdom. The education is required to minimize the risk of forest and land fires; hence it could be used a reference for the Riau government. This study aimed to identify and analyze local wisdom in the community to prevent forest and land fires, including the challenges, potentials, and solutions.